Forehead lesion score for facial nerve paralysis evaluation - Wan Syahirah, Wan Samsudin; Rosdiyana, Samad; Mohd Zaki, Ahmad; Sundaraj, Kenneth (IEEE, 2019)
Facial nerve paralysis is mostly occurring from a temporary or permanent injury to any of facial nerves which drive the failure of facial nerve function. As a consequence, the facial muscles will not receive the necessary signals from the facial nerves in order to function properly and caused the weakness of facial muscles. This facial paralysis affects both verbal and non-verbal communication which has important function and essential element to the development of an individual. The subjective facial nerve assessment involves the assessment of forehead movement which designates whether the lesion is at the level of the upper motor neuron (has movement on both sides) or the lower motor neuron (no movement on paralysed side). An objective assessment of these lesions will give a great impact in managing the symptoms and limiting the sequelae of the paralysis compared to the subjective assessment. A forehead lesion score was developed in this study to differentiate the two types of lesion of facial paralysis, Upper Motor Neuron (UMN) and Lower Motor Neuron (UMN) lesion. Two potential features were extracted from Gabor filter, Mean Amplitude and Local Energy. The best scale and orientation of these features were chosen after the selection of best threshold value. The accuracy percentage by using the Local Energy feature in classifying the UMN is 100% and LMN lesion is 73%. From the results, a forehead lesion score is developed. As a conclusion, this lesion score has the outstanding ability in specifying the facial lesion types and may become a great aid to clinicians for an efficient facial nerve evaluation.